2023
DOI: 10.1111/jen.13193
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of chlorantraniliprole on biological characteristics, detoxifying enzyme activity and gene expression profile in the Allium mongolicum Regel leaf beetle Galeruca daurica (Coleoptera: Chrysomelidae)

Hao Ren,
Hongling Zhang,
Yao Tan
et al.

Abstract: Allium mongolicum Regel leaf beetle, Galeruca daurica (Coleoptera: Chrysomelidae) is rampantly harmful in Inner Mongolia grassland. However, the current management strategies for this pest still heavily rely on chemical control using traditional insecticides or those with novel action. In the study, we conducted an indoor bioassay to evaluate the sublethal effects of chlorantraniliprole on the biological characteristics. Additionally, we assessed the activity of detoxification enzymes, specifically the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The insecticidal effectiveness and suppression of progeny by chlorantraniliprole have been previously evidenced for S. oryzae , exhibiting effectiveness in immediate and delayed mortality [ 33 , 34 ], along with its efficacy and persistence against S. zeamais when combined with lambda-cyhalothrin [ 35 ]. The sublethal effects of this promising compound have been studied for several coleopteran pests [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Nevertheless, the sublethal effects of chlorantraniliprole are yet to be determined for Sitophilus spp., among other significant stored-product pests.…”
Section: Introductionmentioning
confidence: 99%
“…The insecticidal effectiveness and suppression of progeny by chlorantraniliprole have been previously evidenced for S. oryzae , exhibiting effectiveness in immediate and delayed mortality [ 33 , 34 ], along with its efficacy and persistence against S. zeamais when combined with lambda-cyhalothrin [ 35 ]. The sublethal effects of this promising compound have been studied for several coleopteran pests [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Nevertheless, the sublethal effects of chlorantraniliprole are yet to be determined for Sitophilus spp., among other significant stored-product pests.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al. (2024) evaluated the sublethal effects of chlorantraniliprole on the biological characteristics of Galeruca daurica .…”
mentioning
confidence: 99%
“…Ren et al. (2024) found that the upregulated expression of partial CarEs, GST and UGT may participate in the detoxification metabolism of chlorantraniliprole in G. daurica . Yan et al.…”
mentioning
confidence: 99%